Discretionary Medical Cards: Ethical Considerations - Fitzpatrick, Neasa; Hunt, Isabelle; Manley, Éabha; McCrohan, Michael; Nash, Amy; Ryan, Michael; Stokes, Andrew; Toale, Conor (Trinity Student Medical Journal, 2015)
The General Medical Service (GMS) scheme governs access to medical cards in Ireland. A medical card entitles the holder to free health services, including free GP care, inpatient and outpatient hospital services, and prescription medications. Eligibility for medical card cover is based on income, while those whose income is above the maximum threshold for eligibility may be granted a Discretionary card. This is on the basis that to fail to offer these cards would result in ‘exceptional personal and financial burdens arising from medical or social circumstances’ being placed on the applicant. In practice, this scheme covers many people with chronic, life-limiting illnesses. A recent governmental review of the Discretionary medical card scheme led to the cancellation and subsequent re-approval of 15,000 cards, and was met with much controversy both in the Dáil and in the media. Ultimately the ensuing debate centred on the issue of resource allocation, and arguments were made for and against the current means-based system of card allocation versus a disease-based model where factors other than income are taken into account in order to determine an applicant’s eligibility for cover. This article examines some of the arguments both in favour and against these approaches, and questions whether the proposed changes to the scheme, as recommended by the Report of the Expert Panel on Medical Need for Medical Card Eligibility, meet the HSE’s own stated policy targets of equity, fairness, proportionality, openness and accountability, solidarity, and sustainability.